(untitled) (International Journal of Environmental Sciences, 2025)
Background: Metropolitan coastal ecosystems face unprecedented governance challenges from institutional fragmentation and multi-jurisdictional complexities. Jakarta Bay exemplifies these challenges with continuing mangrove degradation despite multiple conservation initiatives across three provinces. Objective: This study develops a comprehensive institutional governance framework for sustainable mangrove management by integrating stakeholder analysis, sustainability assessment, and structural modelling to identify governance gaps and optimal institutional arrangements. Methods: We employed sequential mixed-methods combining stakeholder power-interest matrix analysis (n=23 institutions), Multidimensional Scaling (MDS) sustainability assessment across four dimensions (institutional, ecological, social, economic), and Interpretative Structural Modelling (ISM) for hierarchical governance relationships. Data collection involved structured interviews, focus groups, and policy analysis across Banten, DKI Jakarta, and West Java provinces (October 2023-January 2024). Results: Stakeholder analysis revealed significant power imbalances with 75.8% government dominance, while local communities remain marginalized despite high ecosystem dependence. MDS demonstrated moderately sustainable status: social (72.24%), institutional (60.33%), ecological (59.60%), and economic (55.61%). Leverage analysis identified inter-institutional coordination, regulatory effectiveness, and policy integration as critical factors. ISM revealed hierarchical dependencies requiring foundational institutional arrangements before effective implementation. Conclusions: Current governance arrangements inadequately support sustainable mangrove management in metropolitan coastal zones. Achieving sustainability requires: (1) enhanced multi-stakeholder coordination mechanisms, (2) inclusive governance structures bridging power-interest gaps, and (3) hierarchical institutional development prioritizing foundational elements. This integrated framework provides actionable insights for coastal governance transformation in similar multi-jurisdictional contexts globally.